Congenital Volkmann ischemic contracture – a case report. - Oliveira, A.; Sanches, M.; Selores, M. (European Journal of Pediatric Dermatology, 2011)
Congenital Volkmann ischemic contracture is a rare condition occurring in utero and characterized by ischemia of nerve and muscle caused by raised pressure within a closed fascial space. The Authors report a newborn presenting at birth with a unilateral, well-demarcated necrotic plaque and nerve paralysis. The clinical and histological findings led to the diagnosis of congenital Volkmann ischemic contracture.